1996
DOI: 10.1063/1.117965
|View full text |Cite
|
Sign up to set email alerts
|

Optical excitation of paramagnetic nitrogen in chemical vapor deposited diamond

Abstract: Investigations of polycrystalline chemical vapor deposited diamond films by electron-spin-resonance (ESR), light-induced (L)ESR, and the constant photoconductivity method have identified dispersed substitutional nitrogen (P1 center) as the main paramagnetic form of N incorporated in the CVD diamond. The density of N-related paramagnetic states is strongly affected by illumination and heat treatment. It is found that the P1 center in CVD diamond gives rise to a deep donor state about 1.5 eV below the conduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Our previous EPR study of CVD diamond showed that nitrogen is incorporated mainly into CVD diamond as a substitutional-nitrogen defect (P1 center), and that other various aggregate forms do not exist (15,22). The substitution incorporation of nitrogen results in distortion of the diamond lattice and the observed transition from ͗111͘-to-͗100͘ growth habit in the film.…”
mentioning
confidence: 99%
“…Our previous EPR study of CVD diamond showed that nitrogen is incorporated mainly into CVD diamond as a substitutional-nitrogen defect (P1 center), and that other various aggregate forms do not exist (15,22). The substitution incorporation of nitrogen results in distortion of the diamond lattice and the observed transition from ͗111͘-to-͗100͘ growth habit in the film.…”
mentioning
confidence: 99%
“…The quality of the film is dependent on the nature and the numbers of these defects. If one understands the nature of such defects and is able to control their numbers, one would be able to control the film quality and to use them as a source for coherent luminescence and other purposes.Cathodoluminescence (CL) [10,11], photoluminescence (PL) [2,6], positron-life time spectroscopy (PLS) [12] and electron-spin resonance (ESR) [13] methods are used for vacancy identification.The aim of this work is to show the possibility of making DLC films from liquid gas on metallic substrates and to obtain information about vacancies from UV-visible reflectance of DLC films.Carbon films were deposited on polished 2 × 3cm copper, steel and aluminium substrates from liquid gas (60% Butane and 40% Propane) by dc plasma technique. The substrate temperature was 200 • C and it was grounded.…”
mentioning
confidence: 99%
“…The spectrum of the photoionization cross-section of nitrogen can then be measured over more than three orders of magnitude, thus, nitrogen can be sensitively detected by CPM. Previous studies of substitutional nitrogen in CVD diamond [3,22] reported a wide range of values for the threshold energy of nitrogen donor (e.g. 1.5 eV in [3]), probably due to the above-described effect of hydrogenated surface or due to the nonlinearity of photocurrent spectra in a standard photocurrent measurement.…”
Section: Substitutional Nitrogenmentioning
confidence: 95%